Analisis Perbandingan Tingkat Kepuasan Mahasiswa UIN Sunan Gunung Djati Terhadap Empat E-Wallet (Dana, Ovo, Shoppay dan Gopay) Terbesar di Indonesia - Hafizh Febryansyah Sonjaya; Sani Dwina Putri; Nanda Kuswandari; Ni’matul Aliyah; Mia Lasmi Wardiyah (Moneter : Jurnal Ekonomi dan Keuangan, 2025)
Fundamentally, every individual has two basic needs that must be fulfilled, namely physical and spiritual needs. One of the physical needs that has grown significantly in the digital era is the need for convenience in conducting financial transactions. This study aims to analyze the comparison of satisfaction levels among students of UIN Sunan Gunung Djati toward the four largest e-wallets in Indonesia: Dana, Ovo, ShopeePay, and Gopay. The research employed a quantitative method with a sample size of 20 respondents. The instrument used was a questionnaire distributed via Google Form. As consumers, students not only consider ease of use and low transaction fees, but also pay attention to service quality, security, and transaction speed. Therefore, e-wallet service providers are expected to continuously improve their service quality in order to meet users’ expectations and needs optimally.